Physical fighting among school-attending adolescents in Pakistan: associated factors and contextual influences - Shaikh, Masood; Abio, Anne; Celedonia, Karen; Wilson, Michael (International journal of environmental research and public health, 2019)
Background: Adolescent physical fighting is a problem of public health importance, with varied consequences in the form of school absenteeism, injury, and, in some cases, death. Although research on risk and protective factors exists, most has been conducted in high-income countries. Methods: The 2009 Pakistan Global School-based Health Survey (GSHS) data were used. Logistic regression models were used to determine the associations. Five independent variables were investigated at the individual level (anxiety, suicide planning, truancy, physical activity, and bullying victimization) and four independent variables at the social level (presence of supportive parental figures, presence of helpful peers, extent of social network, and food insecurity). Results: Among adolescents in this study (N = 5177), 20% reported being involved in two or more physical fights, most of whom were males (79.9%). The factors associated with physical fighting were: being male (OR = 2.78); bullying victimization (OR = 3.14); truancy (OR = 1.63), loneliness (OR = 1.44); and suicidality, as evidenced by having a suicide plan (OR = 1.75). Having few close friends (0–2) as opposed to more (>3) was found to be protective against engaging in physical fighting. Conclusion: Risk factors for physical fighting among adolescents in South Asia seem to corroborate with previously-identified risk factors using samples in high-income countries, while protective factors seemed to differ. More research needs to be conducted to understand why certain factors do not have the same protective effect among South Asian adolescents. Aim: The aim of this study was to examine demographic and contextual factors associated with physical fighting among a nationally representative sample in a rapidly developing South Asian context.
Gesehen am 07.05.2020